Effect of SP- 36 Fertilizer and Cow Manure on the Growth and Yield of Barley orJagaq (Setaria italica L.). - Wilson Markoni, Marisi N, Abdul F . (Universitas 17 Agustus 1945 Samarinda, 2017)
The research objectives were: (1) to determine the effect SP-36 fertilizer and cow manure as well as their interaction on the growth and yield of barley; and (2) to obtain appropriate dosages of SP-36 fertilizers and cow manure to obtain better yield of Barley.The research was conducted from February to June 2015 in Sekolaq Darat village, sub district of Sekolaq Darat, West Kutai Regency.It applied 4 x 3 factorial experiment in a Randomized Block Design (RBD) with three replications. The first factor was the dose of SP 36 fertilizer (P) which comprises two levels, namely: no SP-36fertilizer application or control (po), 60 gr/crop (p1) and 120 gr/crop(p2). The second factor was the dose of cow manure (T) consisting of three levels, namely: no cow manure application (to), 500 gr/crop (t1), 750 gr/crop (t2) and 1000 gr/crop(t3). Data analysis used analysis of variance (Anova) and advanced test by using with the Least Significant Difference (LSD) at level of 5%.Result of the reseach showed that: SP-36 fertilizer affected significantly to highly significant on the plant height at the age of 25, 50, 75, and 100 days after planting,number of tiller/cluster and production. The highest yield was attained at the treatment 120 gr/cropSP- 36 fertilizer (p2) namely 0,29. ,meanwhile the lowest one was at the no SP- 36 fertilizer application at SP-36 (po), namely 0.27Effect of cow manure was highly significant on the plant height at 25, 50, 75, and 100 days after planting and number of tiller/cluster. The highest production was attained at the treatment of 1000 gr/crop(t3) namely 0,28meanwhile the lowest one was at the treatment of no manure application(to),namely 0,30.Effect of interaction between SP-36fertilizer and cow manure was significantly different on the plant height at 50, 75 and 100 days after planting, number of tiller/cluster, but it did not affect significantly on the plant height at 25 days after planting and crop production.